some aspects of four-year-plus old stage in the acquisition of Tamil phonology - MS, Thirumalai (Journal of All India Institute of Speech and Hearing, 1972)
The completion of age four for a child is a very crucial stage in its acquisition of language. It is generally agreed that a large amount of syntax is now known to the child and that though the linguistic development continues long after, this development involves mainly such matters as style and possibly semantics but not apparently syntax (Slobin, 1966 & 1971). In other words, having completed successfully the acquisition of the rudiments of a language, the child is now assumed to be involved in processes of acquisition which would enable him to produce utterances matching adult speech.